Tinjauan Hukum Islam terhadap Tradisi Perkawinan Adat Jawa (Adu Pojok) - Hidayah, Laili; Risval Gogou; Muhyidin, Muhyidin (Program Studi Hukum Keluarga Islam (HKI) dan bekerjasama dengan Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LP2M) Institut Pesantren Sunan Drajat Lamongan, 2023)
A Corner Meet marriage is a marriage that is prohibited because the house of the prospective bride and groom meets each other corner of the house. Whereas in Islam it does not regulate the location of the house if you are going to get married, it is important that you meet the criteria that have been determined according to Islam. This research wants to find out how Islamic law reviews the tradition of corner-fighting traditional marriages in Sendangagung Village. As for this study using qualitative methods. This research also includes the category of field research. This method was chosen in order to obtain in-depth and comprehensive research data regarding Javanese traditional marriages fighting corners in Sendangagung Village, Paciran District, Lamongan Regency. The results of this study indicate that from the point of view of Islamic law, corner-to-corner marriages are still valid.